Doha Merchandise Trade Reform : What’s at Stake for Developing Countries? - Anderson, Kym (World Bank, Washington, DC, 2012)
This paper provides new estimates of the global gains from multilateral trade reform and their distribution among developing countries in the presence of trade preferences. Particular attention is given to agriculture, as farmers constitute the poorest households in developing countries but are the most assisted in rich countries. The latest GTAP database (Version 6.05) and the LINKAGE model of the global economy are used to examine the impact first of current merchandise trade barriers and agricultural subsidies, and then of possible reform outcomes from the WTO's Doha Development Agenda. The results suggest moving to free global merchandise trade would boost real incomes in Sub-Saharan Africa proportionately more than in other developing countries or high-income countries, despite a terms of trade loss in parts of that region. Net farm incomes would rise substantially in that and other developing country regions, thereby alleviating rural poverty. A Doha partial liberalization could move the world some way toward those desirable outcomes, but more so the more developing countries themselves cut applied tariffs, particularly on agricultural imports.